Neumann fractional p-Laplacian: Eigenvalues and existence results. (November 2019) - Mugnai, Dimitri; Proietti Lippi, Edoardo
Abstract: We develop some properties of the p -Neumann derivative for the fractional p -Laplacian in bounded domains with general p > 1 . In particular, we prove the existence of a diverging sequence of eigenvalues and we introduce the evolution problem associated to such operators, studying the basic properties of solutions. Finally, we study a nonlinear problem with source in absence of the Ambrosetti–Rabinowitz condition.